RETRACTED: Changes in microalgae composition under the impact of the scallop Mizuhopecten yessoensis - Botsun Liudmila; Markina Zhanna; Maslennikov Sergey; Huo Zhongming (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001